The Influence of Various Substrates on the Survival of Freshwater Lobster (cherax quadricarinatus) in the Open Transport System - Nur, Muhammad; Komariyah, Siti; Haser, Teuku Fadlon (Fakultas Pertanian Universitas Samudra, 2023)
Lobster is one of the leading commodities in Indonesia, with export destinations to Japan, Hong Kong, the USA, and several other countries. In export activities, high mortality is caused by stress during transportation, causing farmers to suffer losses. This research can be an alternative solution to reduce the mortality rate in the transportation of crayfish, which is carried out using a variety of different substrates as transport media. This study aims to determine the effect of using different substrates as filler media for the transport container on the survival of crayfish, which were transported for 6 hours using different substrates, namely paper, raffia rope, coconut fiber, and cotton. The research method used was a completely randomized design. (RAL). The results of this study showed that the transportation of crayfish with different substrates showed survival results on 93% paper substrate, 90% raffia rope, 96% coconut fiber, and 100% cotton. After 10 days of maintenance, the survival of crayfish decreased because the crayfish experienced stress during the transportation test. This was due to a lack of oxygen and moisture in the substrate used during transportation. The highest post-maintenance survival occurred at P4 of 76% and P3 of 75%, while at P1 it was 57% and at P2 it was 67%.